2020
DOI: 10.2139/ssrn.3602333
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of US and EU Economic Policy Uncertainty Shock to Asian Economies in Bad and Good Times

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…None of the previous studies explicitly focused on investigating EPU shock transmission among the Asian countries that showed widespread contagion of the 1997/98 Asian financial crisis. e study that is close to ours is Balcilar et al's study [34], they investigated the impact of EPU shock transmission of US and EU on local EPU and other macroeconomic factors of the Asian economy using quantile vector autoregression (QVAR) but did not examine EPU linkages among the Asian countries. To the best of our knowledge, this is the first study to investigate the transmission of EPU shocks from one Asian country to another using a threshold cointegration approach.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…None of the previous studies explicitly focused on investigating EPU shock transmission among the Asian countries that showed widespread contagion of the 1997/98 Asian financial crisis. e study that is close to ours is Balcilar et al's study [34], they investigated the impact of EPU shock transmission of US and EU on local EPU and other macroeconomic factors of the Asian economy using quantile vector autoregression (QVAR) but did not examine EPU linkages among the Asian countries. To the best of our knowledge, this is the first study to investigate the transmission of EPU shocks from one Asian country to another using a threshold cointegration approach.…”
Section: Introductionmentioning
confidence: 75%
“…Cekin et al [54] investigated the dependence structure of EPU in four Latin American economies (Brazil, Chile, Colombia, and Mexico) and by employing vine copula modelling with various forms of tail dependence, they found significant dependencies in economic uncertainty among the Latin American economies. By adopting QVAR model approach, Balcilar et al [34] extended their examination of external EPU spillovers of US and EU to the local EPU of five Asian economies (China, Hong Kong, Japan, South Korea, and India). ey found that global economic policy uncertainties makeall Asian countries' domestic EPU fragile, except China and Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using both foreign (US and EU) and domestic economic policy uncertainty, we use the quantile spillover estimation approach of Balcilar et al (2020b) to examine how monetary policy effectiveness for these five major Asian economies (China, Hong Kong, India, Japan, and South Korea) changes conditional on different economic policy uncertainty levels. The QVAR model allows investigating potential dynamic heterogeneity not covered by the mean-based impulse response function of mean-based VARs.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a dynamic interaction among multivariate time series by structural inference, whereas constant coefficients characterize the conventional linear VAR model. For spillover dynamics, several authors draw attention to the asymmetric spillover dynamics of macroeconomic shocks (see, e.g., Neftci 1984;Granger 2003;Engle & Manganelli 2004;Balcilar et al 2020b). This feature was pointed out by Fisher (1933) and Keynes (1936) as early as in the 1930s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation